2014
DOI: 10.1007/s11368-014-0861-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of heavy metals in soils of the Yellow River Delta: concentrations in different soil horizons and source identification

Abstract: Purpose The Yellow River Delta, an active land-ocean interaction area, will develop into a large eco-economic region in East China during the coming decade. It is necessary to assess the geochemical features of heavy metals in the soils. The objectives of this research were to evaluate the concentrations and distribution of heavy metals (Cr, Ni, Cu, Zn, Pb, and Cd) in soil profiles of the area and to identify their sources. Materials and methods Horizon samples were collected based on pedogenic features from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The facts that trace element concentrations correlated better with Fe and Al suggests that the elements might have co-precipitated with Fe-Al oxides during the formation in soils [65]. Hernandez et al, 2003 andLi et al, 2014 reported that levels of soil HMs are controlled by concentrations of Al and Fe content [34,45]. Similarly, the significant positive correlation between Pb and Zn in our study can be explained because Pb was found to coexist with Zn in the internal growth of a crystal lattice [1].…”
Section: Heavy Metals Statussupporting
confidence: 55%
“…The facts that trace element concentrations correlated better with Fe and Al suggests that the elements might have co-precipitated with Fe-Al oxides during the formation in soils [65]. Hernandez et al, 2003 andLi et al, 2014 reported that levels of soil HMs are controlled by concentrations of Al and Fe content [34,45]. Similarly, the significant positive correlation between Pb and Zn in our study can be explained because Pb was found to coexist with Zn in the internal growth of a crystal lattice [1].…”
Section: Heavy Metals Statussupporting
confidence: 55%
“…Hence the importance of studying the water quality by estimating the physicochemical quality of water which cannot be measured in a single way, but, by a set of parameters of different properties will be of our high interest Previous works focused on the water quality by measuring different parameters such as total dissolved solids, TDS and the concentration of phosphate sulfate, ammonia and other nutrients. Other researchers studied the effect of seasonal factors on the concentration of pollutants in the surface water especially the runoff during the periods of flooding [7] [8] [9] [10]. A relation between the nutrient loading to the rivers and the ecosystem has been reported by the Millennium Ecosystem Assessment [11].…”
Section: Introductionmentioning
confidence: 99%
“…But after entering the soil solution, metal oxide forms transformed into mobile forms which are capable of migration in the soil profile. The depth distribution of metals and their mobility depends on some soil properties: pH, mineral composition and clay content, redox conditions and soil organic carbon (Li et al 2014;Shaheen and Rinklebe 2014;Proust 2015).…”
Section: Introductionmentioning
confidence: 99%